THE STAGES OF ACCOUNTING POLICIES FORMATION - Kafka S.М. (The actual problems of regional economy development, 2017)
In the article the research of the existing scientists’ approaches to the procedure of the company accounting policy formation have been done, their critical analysis has been made, the major groups of issues and problems raised in scientific works have been found out, and those ones, which require the further up-to- date refinement, have been identified: the formation of the stages in projecting of the accounting policy in accordance with requirements of legislation. For the purposes of study the methods of analysis and synthesis, systematic approach to study the process of developing the company accounting policy and logical method and simulation to systematize the information support of the processes mentioned have been used. As a result, a comprehensive approach to the formation of accounting policy has been worked out, the author's vision of the stages in projecting of the accounting policy and their contents has been also proposed and disclosed in details.